ChemInform Abstract: Pd‐Catalyzed Enantioselective Intramolecular α‐Arylation of α‐Substituted Cyclic Ketones: Facile Synthesis of Functionalized Chiral Spirobicycles. Issue 34 (August 2015) - Fan, Lulu; Takizawa, Shinobu; Takeuchi, Yoshiki; Takenaka, Kazuhiro; Sasai, Hiroaki
Abstract Various chiral spirocyclic ketones are enantioselectively obtained via Pd‐catalyzed intramolecular α‐arylation reactions of cyclic ketones.